Sex- and age-related morphological and functional differences in the skull of Eira barbara (Linnaeus, 1758) (Carnivora, Mustelidae) - Fernando Araujo Perini; Fernando L. Sicuro (PeerJ)
Background Morphological differences related to age and sex have been extensively documented in Nearctic and Palearctic mustelids, largely due to the interest in the commercial management of species such as martens and fishers. However, sexual dimorphism and ontogenetic development in Neotropical species, such as the tayra (Eira barbara), remain poorly studied. Methods We investigated the skull development and sexual differences in E. barbara through qualitative and morphometric analyses of 376 skull specimens from museum collections. Specimens were classified into four age classes based on tooth eruption, cranial suture closure, and skull morphology. Linear measurements were used to assess biomechanical parameters related to the masticatory function, including temporal and masseter muscle force indices. Results The results show that male and female tayras follow two distinct growth pathways. While juveniles (Age Classes I–II) share nearly identical skull proportions, males rapidly surpass females in size and robustness by the subadult stage (Age Class III). Fully mature males (Age Class IV) develop broader zygomatic arches, thicker sagittal crests, and significantly stronger bite forces driven by enlarged temporal muscles. On the other hand, E. barbara adult females exhibit a narrower post-orbital constriction and palatal region which denotes distinct ontogenetic trajectories between males and females. Multivariate statistical analyses (principal component analysis/discriminant function analysis) confirmed these morphological trends, highlighting allometric growth patterns and functional differences in masticatory biomechanics. Males exhibit greater bite force, particularly in the temporal muscle system, which may be linked to territorial defense or mating behaviors. These findings align with patterns observed in other Guloninae species, such as fishers (Pekania pennanti) and wolverines (Gulo gulo), but highlight unique aspects of E. barbara’s tropical ecology, including non-seasonal breeding, flexible growth patterns, and broad habitat use. Additionally, tayras’ asynchrony in sexual maturity and sexual dimorphism in skull biomechanics may be related to distinct ecological roles for the sexes. We hypothesize that these differences are adaptative responses to the dynamic and resource-rich environments of the Neotropics. Our work underscores the role of ontogenetic and sexual variation in understanding the evolutionary and ecological adaptations of Neotropical mustelids, providing new light on E. barbara’s morphology and masticatory function.